Optimization for Lutein Extract and Antioxidant Activity from Marigold Flowers (𝙏𝙖𝙜𝙚𝙩𝙚𝙨 𝙚𝙧𝙚𝙘𝙩𝙖 L.) Using Ultrasonic Assisted Extraction - Wilailak, Nipathon; Narkprasom, Nukrob; Tanongkankit, Yardfon; Nookong, Mookarin; Sri-ngernyuang, Chawakorn; Narkprasom, Kanjana (Burapha Science Journal, 2025)
Background and Objectives : Marigold (Tagetes erecta L.) is an economically valuable flowering plant that can be cultivated year-round. It is recognized as a rich natural source of lutein, a carotenoid compound that plays a significant role in reducing the risk of age-related macular degeneration. Moreover, lutein exhibits antioxidant properties that help protect cells from oxidative damage, potentially reducing the risk of chronic diseases. However, since the human body cannot synthesize lutein, it must be obtained through dietary intake. Conventional methods of lutein extraction typically rely on organic solvents such as hexane and acetone. Although effective, these solvents are hazardous to both human health and the environment. Therefore, this study aims to develop a safer and more sustainable method for extracting lutein and antioxidant compounds from marigold petals. The proposed method utilizes ultrasound-assisted extraction (UAE) combined with ethanol, a food-grade solvent known for its environmental friendliness and low toxicity. The research specifically focuses on identifying optimal extraction conditions by evaluating three critical parameters: ultrasonic amplitude, extraction time, and ethanol concentration. The goal is to maximize extraction efficiency while preserving the bioactive properties of the target compounds. Methodology : Fresh marigold flowers were first washed three times with reverse osmosis (RO) water to remove impurities and potential contaminants. The flowers were then air-dried in the shade to reduce initial moisture levels. Once adequately dried, the petals were separated from the calyx and subjected to freeze-drying at -40 °C under vacuum pressure not exceeding 10 Pa until the moisture content dropped below 10%. The dried marigold petals were ground into a fine powder using a high-speed multifunctional dry grinder operating at 25,000 rpm. The powder was then mixed with ethanol in varying concentrations and subjected to ultrasound-assisted extraction using a specialized ultrasonic device. The experimental design was based on the Box-Behnken Design (BBD), a response surface methodology that allows for the assessment of multiple variables and their interactions. The study investigated three independent variables: ultrasonic amplitude (20%, 40%, and 60%), extraction time (5, 15, and 25 minutes), and ethanol concentration (40%, 60%, and 80%). The extracted samples were analyzed for lutein content using High-Performance Liquid Chromatography (HPLC) and for antioxidant activity using the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay. Data from the experiments were subjected to Analysis of Variance (ANOVA) using the SPSS software to identify statistically significant factors and interactions affecting the extraction efficiency. Main Results : The study revealed that both ethanol concentration and extraction time significantly influenced the efficiency of lutein and antioxidant extraction. Ethanol, being a semi-polar solvent, has the ability to solubilize both polar and non-polar bioactive compounds. This characteristic enables it to co-extract phenolic compounds and flavonoids, which are known to be present alongside lutein in marigold petals. These compounds collectively contribute to the overall antioxidant capacity of the extract. Increasing the extraction time up to an optimal level facilitated better mass transfer and diffusion of bioactive compounds from plant tissues into the solvent. However, prolonged extraction times beyond the optimal range led to increased internal system temperatures, which may promote oxidative degradation, especially in heat-sensitive compounds like lutein. This degradation ultimately results in lower yields. Regarding ultrasonic amplitude, the study found that higher amplitudes generally enhanced the release of lutein from plant tissues. This is attributed to the cavitation effect generated by ultrasonic waves, where microbubbles collapse violently, causing the rupture of plant cell walls and facilitating the release of intracellular compounds. Nevertheless, excessive amplitude may lead to elevated pressures and temperatures within the extraction medium, which could again result in the degradation of sensitive compounds. Interestingly, while amplitude had a noticeable effect on lutein yield, it did not significantly influence the antioxidant activity of the extracts. This could be due to the insufficient intensity of the ultrasonic treatment to disrupt cellular structures enough to release additional antioxidant compounds beyond those already extracted by ethanol. Conclusions : Marigold flowers are a valuable botanical source of lutein and antioxidant compounds, both of which can be effectively extracted using ultrasound-assisted extraction techniques. Based on response surface methodology analysis, the optimal extraction conditions were determined to be 42% amplitude, 16 minutes of extraction time, and 80% ethanol concentration. Under these optimized conditions, the maximum lutein yield was 7.06 mg per gram of sample, and the highest antioxidant activity observed was 79.82%. The ANOVA results demonstrated a high degree of model fit and prediction reliability, with R² values of 0.9691 for lutein content (Y1) and 0.9943 for antioxidant activity (Y2). Furthermore, the Significance F values were found to be less than 0.001, indicating the statistical significance and robustness of the predictive models developed through the Box-Behnken Design. This study underscores the potential of ultrasound-assisted extraction using ethanol as a green, efficient, and scalable technique for extracting valuable bioactive compounds from marigold flowers. Not only does it offer a safer alternative to traditional organic solvents, but it also supports sustainability goals by minimizing environmental impact and reducing extraction time and energy consumption.